Identifying emotional intelligence skills of Turkish clinical nurses according to sociodemographic and professional variables. Issue 7 (23rd February 2016) - Kahraman, Nilgün; Hiçdurmaz, Duygu
Abstract : Aims and objectives: This study aimed to identify the emotional intelligence skills of Turkish clinical nurses according to sociodemographic and professional variables. Background: Emotional intelligence is "the ability of a person to comprehend self‐emotions, to show empathy towards the feelings of others, and to control self‐emotions in a way that enriches life." Nurses with a higher emotional intelligence level offer more efficient and professional care, and they accomplish more in their social and professional lives. Design: We designed a descriptive cross‐sectional study. The Introductory Information Form and the Bar‐On emotional intelligence Inventory were used to collect data between 20th June and 20th August 2012. Method: The study was conducted with 312 nurses from 37 hospitals located within the borders of the metropolitan municipality in Ankara. Results: There were no significant differences between emotional intelligence scores of the nurses according to demographic variables such as age, gender, marital status, having children. Thus, sociodemographic factors did not appear to be key factors, but some professional variables did. Higher total emotional intelligence scores were observed in those who had 10 years or longer experience, who found oneself successful in professional life, who stated that emotional intelligence is an improvable skill and who previously received self‐improvement training. Interpersonal skills were higher in those with a graduate degree and in nurses working in polyclinics and paediatric units. Conclusions: These findings indicate which groups require improvement in emotional intelligence skills and which skills need improvement. Additionally, these results provide knowledge and create awareness about emotional intelligence skills of nurses and the distribution of these skills according to sociodemographic and professional variables. Relevance to clinical practice: Implementation of emotional intelligence improvement programmes targeting the determined clinical nursing groups by nursing administrations can help the increase in emotional intelligence.